“Ethical and Legal First Amendment Implications of FBI v. Apple: A Commentary on Etzioni’s ‘Apple: Good Business, Poor Citizen?’” - Nielsen, Richard P. (Journal of business ethics, 2018)
This commentary proceeds as follows. First, it is argued from both ethical and legal perspectives through an analysis of Court precedents that Etzioni’s has improperly developed a too narrow First Amendment interpretation and conclusion that Apple should comply with the FBI’s demand to provide the FBI with a key to open iPhones. That is, broad First Amendment considerations and not solely narrow First Amendment “compelled speech” or only Fourth Amendment privacy issues are offered and analyzed from both ethical and legal perspectives. A key point here is that broad First Amendment considerations protect, with exceptions, political and ethical discretion space for “Press” organizations to exercise, or not, ethical responsibilities, including rights to publish or not publish information and opinions, rather than compliance with government orders to publish or not publish. Further, Court cases are discussed from both legal and ethical perspectives where the Courts have established that social media organizations such as Facebook and Twitter do and should have broad First Amendment protection of free expression and peaceful assembly as traditional media such as newspapers have. It is suggested that Apple can and should be considered a social media organization. In addition, special First Amendment protection and limitations concerning national security are analyzed. Second, it is suggested that Etzioni’s point that Apple protected its clients soley for “business profitability” reasons is also a too narrow interpretation since there are more complex, mixed, and combined ethical and political-economic reasons for protecting clients and First Amendment protections. Third, the philosopher Paul Ricoeur’s ethics process responsibility framework concerning relationships between ethics and law and the need for an ethics responsibility rather than a compliance approach, which is similar to Brandeis’ legal ethics approach, is compared with and offered as an alternative to Etzioni’s compliance based “Liberal communitarian” approach. It is suggested that the difference between the Rocoeur and Etzioni approaches is similar to the difference between compliance and ethics responsibility process programs in organizations.